Genome-wide identification of alternative splicing and splicing regulated in immune infiltration in osteosarcoma patients - Dai, Zhibing; Sun, Yachao; Maihemuti, Maierdanjiang; Jiang, Renbing (Frontiers in Genetics, 2023)
Background: Osteosarcoma typically occurs in adolescents, and the survival rate of patients with metastatic and recurrent osteosarcoma remains low. Abnormal regulation of alternative splicing is associated with the development of osteosarcoma .However, there is no genome-wide analysis of the function and regulatory mechanisms of aberrant alternative splicing associated with osteosarcoma. Methods: Published transcriptome data of osteosarcoma (GSE126209) derived from osteosarcoma patient tissue were downloaded. Gene expression profiling by high-throughput sequencing was performed on 9 normal samples and 10 tumour samples for genome-wide identification of osteosarcoma-related alternative splicing events. The potential function of osteosarcoma-associated alternative splicing events was examined by immunoinfiltration and correlation analysis. Regulation of aberrantly expressed RBPs related to alternative splicing in osteosarcoma was clarified by co-expression analysis. Results: There are 63 alternative splicing events which highly credible and dominant were identified. GO enrichment analysis indicated that alternative splicing may be closely related to the immune response process. Immune infiltration analysis showed significant changes in the percentages of CD8 T cells, resting memory CD4 T cells, activated memory CD4 T cells, monocytes, resting dendritic cells and activated mast cells in tumours compared to normal tissues, indicating involvement of these immune cell types in the occurrence of osteosarcoma. Moreover, the analysis identified alternative splicing events that were co-altered with resting memory CD4 T cells, resting dendritic cells and activated mast cells, events that may be associated with regulation of the osteosarcoma immune microenvironment. In addition, a co-regulatory network (RBP-RAS-Immune) of osteosarcoma-associated RBPs with aberrant alternative splicing and altered immune cells was established. These RBPs include NOP58, FAM120C, DYNC1H1, TRAP1 and LMNA, which may serve as molecular targets for osteosarcoma immune regulation. Conclusions: These findings allow us to further understand the causes of osteosarcoma development, and provide a new research direction for osteosarcoma immunotherapy or targeted therapy.